Enaction, relevance realisation and wisdom: establishing a theoretical framework for contemplative education - Barratt, Sāgaradevī (Frontiers in Education, 2025)
Interest in contemplative education in higher education has grown significantly over the last two decades. Much of this work has focused on mindfulness interventions and their impact on the wellbeing and academic outcomes of students. However, there has been considerable diversification in how contemplative practice has been applied, particularly in university contexts where educators often have greater autonomy in the design and delivery of teaching. In this paper I argue that for contemplative education to develop, a theoretical framework is important, particularly if robust research is going to build an evidence base for informing practice. Useful links have started to be drawn to other educational theories such as social and emotional learning and transformative learning theory but they do not yet point to the depth of learning made possible through the integration of contemplative practice into teaching. This paper uses the lens of enaction to explore contemplative education and draws on the concepts of relevance realisation and wisdom to present a conceptual model of contemplative education that could support future research and pedagogical integration by explaining how contemplative practices may take effect. This paper offers fresh theoretical insights to stimulate discussion about how contemplation can support the development of wisdom and what this means for higher education.